NOVICE EFL WRITERS' INTERFERENCES IN MULTICULTURAL CLASS: FEELINGS OF ANXIOUS TO THE WRITING PERFORMANCE - Ike Dian Puspita Sari; Indrawati Pusparini; Anita Kurnia Rachman (Jurnal Pendidikan (Teori dan Praktik), 2024)
In writing academically, EFL students experience different levels of anxiety for each EFL student. This study aims to measure the general level of writing anxiety experienced by EFL students. In addition, it will specifically measure whether there is an influence on the level of writing anxiety of EFL students with several factors, such as gender, length of study, and region. There are other things to look for, which are related to the type of writing anxiety experienced by EFL students, as well as what factors have a major contribution to this writing anxiety. This study used a quantitative approach by conducting a survey of 58 EFL students divided into 3 academic years, where they took basic writing, intermediate writing and advanced writing courses. The results show that the level of student anxiety is average, with cognitive anxiety (M=18.93) being the highest among somatic anxiety (M=18.30) and avoidance behavior anxiety (M=17.96). Then, the factor that most influenced EFL students' writing anxiety was the problem of linguistic factors (9.3%), which was then followed by writing process under constraint (8.5%). However, EFL students did not feel anxious tothe writing test and writing assessment which percentage of each issue was 7.3%.